Reconstructing culture through art- for the memory of Sámi Noaidi Aikia Aikianpoika - Joy, Francis (2018)
The practice of Sámi shamanism is a cultural phenomenon, which has a long and ambiguous history throughout Sápmi, which are primarily, the northernmost areas of Norway, Sweden, Finland and north-west Russia, where the Sámi live, who are Europe’s Indigenous People. Because, Sámi spirituality is undergoing a revival throughout the aforementioned countries within the past two decades, there is a rise in interest in this topic. In scholarly discourses both past and present, much emphasis has been placed on the Sámi noaidi, the religious specialist within Sámi society who have been the subjects of persecution and repression by evangelical priests and missionaries of the Christian Churches for over 800 years. In relation to these events, the subject matter of the proposed study is concerned with local history and cultural memory with regard to circumstances as such, conveyed through an art exhibition called Multiformes, at Lapin Maakuntamuseon (Provisional Museum of Lapland), Rovaniemi, Finland, which opened on the 26.01.2018 and will remain there until 15.4.2018. The research undertaken is in connection with the story of the fate of Sámi noaidi Aikia Aikianpoika who recieved a death sentence in court for alleged crimes of witchcraft in 1671. The material brings together past, present and future for evaluating in what ways the noaidi’s memory has recently been reconstructed in one part of the art exhibition by one of his descendants, and how this is important for both culture and heritage regarding local history. In short, the foundation of investigation is centralized on the 17th century around the areas of Kitka and Kemi, when Finland was a part of the Kingdom of Sweden, Kitka being where the noaidi lived and Kemi where his trial took place.